MULTIGRADING CLASSES APPLICATION AND TEACHER’S PREPARATION IN LOW ENROLMENT SCHOOLS IN MALAYSIA - K., Ponniah; T.M, Thannimalai.; T.M, Thannimalai.; F.M, Nawastheen. (International Journal of Psychosocial Rehabilitation, 2020)
This study was designed and aimed at identifying the possibilities of implementing multi- graded teaching in low enrolment primary schools in Malaysia. This study is an attempt to introduce the multi- graded teaching to the teachers in low enrolment schools in Malaysia to overcome the issues of: limited class, teacher and student shortage, teacher’s absentness, lack of teaching materials or schools with lack of teachers with a huge number of students. The researcher found that multi-graded teaching has a unique teaching method which had been proven effective by many scholars. The multi-graded teaching was different form mono-graded teaching wherein for multi-graded classes the teacher will teach a two or three-grade students in the same class but the mono-grade teacher will only teach one grade student at one time. Many scholars has proven that after implementing the multi-graded teaching in their classes, the performance of the students were improved in terms of: academic, social and behaviours. Thus, this study encouraged the multi-graded teaching to all Malaysian low enrolment primary schools and in order to persuade the low enrolment school teachers to adopt and adapt this new pedagogy system which will be cost effective and time saving. The finding of this study found that almost all low enrolment teachers gave positive perceptions and responses toward the implementation of multi-grades teaching in low enrolment primary schools. Meanwhile, the researcher found that few low enrolment teachers did not have wide knowledge about multi-graded education thus they thought that to implement successful multi-graded teaching in low enrolment school need specific teaching tool, proper guidance and infrastructures. Thus, multi grading classes was most suitable to apply in Malaysia especially low enrolment school which has low student or low teacher’s problems. The research outcome was expressed that multi grading classes will give positive impact on student learning performance. However, from teachers’ point of view who worked in low enrolment school given positive feedback on applying multi grading teaching in low enrolment school. Thus, this research urge multi grading teaching will be a new approach that must to be followed by problematic school which has low number of teacher and students which can be used multi grading classes as alternative teaching that could replace the existing teaching method that widely applied in many low enrolment schools